2010
DOI: 10.1590/s0100-204x2010000600009
|View full text |Cite
|
Sign up to set email alerts
|

Frações de fósforo no solo após sucessivas aplicações de dejetos de suínos em plantio direto

Abstract: Resumo -O objetivo deste trabalho foi quantificar as frações de acumulação de fósforo em solo submetido a sucessivas aplicações de dejetos líquidos de suínos (DLS) em sistema de plantio direto. Em Santa Maria, RS, doses de 0, 20, 40 e 80 m 3 ha -1 de DLS foram distribuídas a lanço por sete anos agrícolas, antes do plantio de cada cultivo de inverno ou verão, em Argissolo Vermelho arenoso, totalizando 0, 584, 1.168 e 2.336 kg ha -1 de P aplicado via dejetos. O solo foi coletado nas camadas 0-2, 4-6, 8-10, 14-16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
41
0
15

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 25 publications
10
41
0
15
Order By: Relevance
“…and 3.0, 0.15 and 2.6 % of the total applied through NPK, respectively. These low values of P transferred via surface runoff in the different nutrient sources are similar to the results obtained by Bertol et al (2010), who observed P transfer via surface runoff of less than 15 % of the total applied and suggested that the P remains accumulated in the soil surface layer, as verified in the present study (Table 2) and in other studies (Adeli et al, 2008;Scherer et al, 2010;Ceretta et al, 2010a;Guardini et al, 2012a). Nevertheless, after successive manure applications, there is a tendency for saturation of adsorption sites of the reactive particles of the soil.…”
Section: P Transfer Via Surface Runoffsupporting
confidence: 92%
See 2 more Smart Citations
“…and 3.0, 0.15 and 2.6 % of the total applied through NPK, respectively. These low values of P transferred via surface runoff in the different nutrient sources are similar to the results obtained by Bertol et al (2010), who observed P transfer via surface runoff of less than 15 % of the total applied and suggested that the P remains accumulated in the soil surface layer, as verified in the present study (Table 2) and in other studies (Adeli et al, 2008;Scherer et al, 2010;Ceretta et al, 2010a;Guardini et al, 2012a). Nevertheless, after successive manure applications, there is a tendency for saturation of adsorption sites of the reactive particles of the soil.…”
Section: P Transfer Via Surface Runoffsupporting
confidence: 92%
“…That is because P is predominantly found in inorganic form in the manure, readily available to plants. This may be seen in figure 1, where the greatest available P contents were observed in the first days of soil incubation, which indicates that a large part of the P present in the manure is found in the inorganic form, which is the predominant form of accumulation in soils treated with manure (Chardon et al, 2007;Gatiboni et al, 2008;Ceretta et al, 2010a;Guardini et al, 2012a;Lourenzi et al, 2013). Furthermore, the absence of tilling in the no-tillage system favors P accumulation in the soil surface layers because, in the soil, the P may be adsorbed to the surface of functional groups of reactive particles, normally forming inner sphere complexes (specific adsorption) (Barrow, 1999).…”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…The movement of P in the profile probably occurred in soluble form, in view of the high concentrations found in the soil solution (Figure 1), by the water flow through the profile. But, although to a lesser degree, the migration of P in particulate form and by bioturbation may also have occurred, which is the movement of particles in biopores (Ceretta et al, 2010a). The migration of P in the profile, especially in soils with sandy texture, as in the Typic Hapludalf of this study, the risk of subsurface water contamination is greater, especially in soils where the water table is shallower, making the water unfit for human consumption (Sorensen and Rubaek, 2012;Girotto et al, 2013;Lourenzi et al, 2014).…”
Section: Discussionmentioning
confidence: 66%
“…When these sites are saturated, P can be leached by water, percolating through the soil profile. Losses of P by leaching or surface runoff, when attached to soil colloids, present a risk of degradation of groundwater and surface waters, respectively (Ceretta et al, 2010). Berwanger et al (2008) found that pig slurry application at the surface of an Ultisol soil resulted in nutrient loss by surface runoff, while Djodjic et al (2004) reported nutrient losses by leaching.…”
Section: Soil Chemical Propertiesmentioning
confidence: 99%